TEORI KAUSALITAS ARISTOTELIAN - Widiadharma, Novian; Lasiyo; Tjahjadi, Sindung (UIN Sunan Kalijaga Yogyakarta, 2023)
Abstract Causality is a fundamental concept in philosophy because it is important for understanding how things work in the world. The concept of four causes in Aristotle's philosophy, namely material, formal, efficient, and final causes, has an important role in the development of Islamic philosophy. This article will only focus on Aristotle's view as a starting point in the Physics and Metaphysics, especially those that explicitly discuss the problems of the four causes. The results are as follows: material cause (causa materialis) is the matter or physical substance from which an object or things are made. It is an important component of the nature of things, but is not sufficient on its own to explain the full nature of an object or phenomenon. Formal cause (causa formalis) is the special patterns, designs, or arrangements that give something an identity and determine its characteristic properties and behavior. It is a cause that helps us understand the intent or purpose of an object or phenomenon. Efficient cause (causa efficient) is agent or process that produce changes or movements in an object or phenomenon. It is the causes that help us understand the behavior and development of objects and phenomena. The final cause (causa finalis) is the purpose, end or purpose of an object or phenomenon, which gives it direction and meaning. It is cause that helps us understand the nature of things, and is important for understanding the purpose or inherent purpose of objects and phenomena. Keyword: Aristotelian cause; material causes; formal cause; cause efficient; final cause Abstrak Kausalitas adalah konsep fundamental dalam filsafat karena penting untuk memahami bagaimana sesuatu bekerja di dunia. Konsep empat sebab dalam filsafat Aristoteles, yaitu sebab material, formal, efisien, dan final, memiliki peran penting dalam perkembangan filsafat Islam. Tulisan hanya akan memfokuskan diri pada pandangan Aristoteles sebagai titik pijakan dalam teks Physics dan Metaphysics terutama yang secara eksplisit membahas masalah empat kausa tersebut. Hasilnya adalah sebagai berikut: penyebab material (causa materialis) adalah materi atau substansi fisik yang darinya suatu objek atau benda dibuat. Ini adalah komponen penting dari sifat benda, tetapi tidak cukup dengan sendirinya untuk menjelaskan sifat penuh dari suatu objek atau fenomena. Penyebab formal (causa formalis) adalah pola, desain, atau pengaturan khusus yang memberikan identitas pada sesuatu dan menentukan sifat dan perilaku karakteristiknya. Ini adalah penyebab yang membantu kita memahami maksud atau tujuan dari suatu objek atau fenomena. Penyebab efisien (causa efficient) adalah agen atau proses yang menghasilkan perubahan atau pergerakan pada suatu objek atau fenomena. Ini adalah penyebab yang membantu kita memahami perilaku dan perkembangan objek dan fenomena. Penyebab final (causa finalis) adalah maksud, akhir atau tujuan dari suatu objek atau fenomena, yang memberinya arah dan makna. Ini adalah penyebab yang membantu kita memahami sifat benda, dan penting untuk memahami tujuan atau tujuan inheren dari objek dan fenomena. Kata kunci: Kausa Aristotelian; sebab material; sebab formal; sebab efisien; sebab final